Terpaan Pesan Iklan Anti Kekerasan Radio PRAMBORS dan Interaksi Peer Group terhadap Sikap Anti Kekerasan Remaja - Fitrianti, Ayang (Jurnal The Messenger, 2017)
Characteristic teen expressive, always curious and receptive to new values in this era of globalization should be directed and escorted on positive things like Prambors Radio which serve Ad Links anti Violence. Therefore, this study aims to determine the extent of Exposure to Violence Ad Links Prambors Radio and Peer Group of the Attitudes of Teen Violence. The method used in this research is quantitative method, explanatory paradigm of positivistic. The theory used in this study is the Social Learning Theory by Bandura and the theory of Hierarchy Effect Model. This study uses survey respondents were 116 respondents who are listeners Prambors Radio. Based on this research, it can be concluded that the inundation Ad Links Anti Violence positively related to Attitude Teen Violence. In addition the results also showed that interaction with the Peer Group also showed a significant positive correlation to the attitude of Teen Violence.